2013
DOI: 10.1055/s-0040-1703711
|View full text |Cite
|
Sign up to set email alerts
|

Study of Accessory Foramen Transversaria in Cervical Vertebrae

Abstract: The cervical vertebrae presents foramen transversaria in each transverse process. In all but the seventh cervical vertebra, the foramen normally transmits vertebral artery and vein and a branch from the cervicothoracic ganglion.140 cervical vertebrae were studied. Variations were noticed in the number of foramen transversarium unilaterally and bilaterally. Variations in foramen transversarium may indicate the variation in course of vertebral arteries

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 2 publications
2
4
0
1
Order By: Relevance
“…Together, they form the basilar artery [18]. [1,[19][20][21]. These results comply with our study's findings.…”
Section: Discussionsupporting
confidence: 93%
“…Together, they form the basilar artery [18]. [1,[19][20][21]. These results comply with our study's findings.…”
Section: Discussionsupporting
confidence: 93%
“…Rathnakar et al reported the incidence of double FT as a total of 5.7% (unilateral 3.6%, bilateral 1.42%) out of 140 vertebrae. 8 We also found the incidence of double FT 5.7% in our population, which is similar to this study.…”
Section: Discussion: Double Foramen Transversarium (Ft) Issupporting
confidence: 91%
“…In any case, our finding of DTF in infantile cervical vertebrae contributes to a greater clinical meaning of this anatomical variant in today's paediatric population, especially because DTF might be associated with a greater risk of vertebral artery sectioning and cerebral infarction due to osseous cervical anomalies (Sedney and Rosen, 2011). Clinical importance of DTF contrasts with a lack of data on DTF prevalence in today's paediatric population, since research studies has exclusively focused on both present adult populations (Aydınoğlu et al, 2001;Das et al, 2005;Sanchis-Gimeno et al, 2005;Sharma et al, 2010;Murlimanju et al, 2011;Agrawal et al, 2012;Chandravadiya et al, 2013;Rathnakar et al, 2013;Katikireddi and Setty, 2014) and ancient adult populations from archaeological samples (Taitz et al, 1978;Nagar et al, 1999;Kaya et al, 2011). Since vertebrae with DFT analyzed in this study were ancient, fragile and incompleted, it was not possible to study DFT prevalence in our subject population.…”
Section: Discussionmentioning
confidence: 99%